Koneksi Politik dan Penghindaran Pajak Perusahaan Manufaktur Indonesia (Lembaga Pengembangan Kinerja Dosen, 2023)
Tax avoidance can be defined as a strategy taken by a company to minimize the company's tax expense by taking legal action through exploiting loopholes in tax regulations. The existence of the implementation of a self-assessment system in fulfilling tax obligations is a gap for taxpayers to take tax avoidance actions. This study aims to examine and analyze the effect of political connections through government involvement in corporate boards and political connections through state ownership on tax avoidance. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. The research sample was obtained using a purposive sampling method with a total sample of 49 samples with 245 observations. Data were analyzed using multiple regression analysis. The results of the study show that political connections through government involvement in company boards are able to minimize corporate tax avoidance actions, while political connections through government share ownership do not affect corporate tax avoidance actions